2014
DOI: 10.1002/jat.3043
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of L‐ascorbic acid, N‐acetylcysteine and apocynin on neomycin‐induced hair cell loss in Zebrafish

Abstract: Hair cells are highly sensitive to environmental insults and other therapeutic drugs. The adverse effects of drugs such as aminoglycosides can cause hair cell death and lead to hearing loss and imbalance. The objective of the present study was to evaluate the protective activity of L-ascorbic acid, N-acetylcysteine (NAC) and apocynin on neomycin-induced hair cell damage in zebrafish (Danio rerio) larvae at 5 days post fertilization (dpf). Results showed that the loss of hair cells within the neuromasts of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, it is known that the injection of 10 −3 mol/L neomycin (2 ml) into the unilateral cochlea via the round window membrane induces the loss of all homolateral cochlear and vestibular hair cells and hearing and vestibular function abnormalities in adult C57BL/6 mice [ 41 ]. ROS formation by neomycin is reported to play a role in neomycin-induced ototoxicity, and antioxidant compounds is assumed to inhibit intracellular apoptotic pathways triggered by neomycin [ 42 , 43 ]. Our previous reports also demonstrated that neomycin elevated ROS formation and induced apoptosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that the injection of 10 −3 mol/L neomycin (2 ml) into the unilateral cochlea via the round window membrane induces the loss of all homolateral cochlear and vestibular hair cells and hearing and vestibular function abnormalities in adult C57BL/6 mice [ 41 ]. ROS formation by neomycin is reported to play a role in neomycin-induced ototoxicity, and antioxidant compounds is assumed to inhibit intracellular apoptotic pathways triggered by neomycin [ 42 , 43 ]. Our previous reports also demonstrated that neomycin elevated ROS formation and induced apoptosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…One strategy for preventing damage to hair cells is to administer otoprotective drugs that counteract cellular injury from otherwise beneficial drugs (Coffin et al, 2010 ; Ou et al, 2010 ; Esterberg et al, 2013 ). Otoprotectants mainly work by interfering with antibiotic uptake (Hailey et al, 2012 ; Ou et al, 2012 ) or inhibiting generation of reactive oxygen species (Le Prell et al, 2007 ; Wu et al, 2014 ). The antioxidant epicatechin protects both mammalian and zebrafish hair cells against cisplatin damage and decreases reactive oxygen species generation (Kim et al, 2008 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…We next investigated the impact of antioxidant treatment upon KR-mediated ROS generation. The potent ROS scavenging compound Nacetylcysteine (NAC) has been shown to successfully rescue overall cellular and oxidative stress [35] , [36] , [37] . Application of increasing H 2 O 2 concentrations (1 mM, 2 mM, 5 mM, and 10 mM) led to significant and dose-dependent increase in ROS-mediated fluorescence in 3 dpf zebrafish embryos ( Fig.…”
Section: Resultsmentioning
confidence: 99%